An Empirical Examination of Religious/Spiritual Struggle Among Israeli Jews. Issue 1 (2nd January 2016) - Abu-Raiya, Hisham; Pargament, Kenneth I.; Weissberger, Andra; Exline, Julie
Abstract : The current investigation examined the prevalence, predictors, and psychological implications of religious and spiritual (r/s) struggles among a sample of Israeli-Jewish university students. R/s struggle was assessed by the Religious and Spiritual Struggles (RSS) Scale. This is a newly constructed scale that assesses a wide array of r/s struggles. The RSS is composed of six factors of struggles: Divine, Doubt, Demonic, Interpersonal, Moral, and Ultimate Meaning. Confirmatory factor analysis of the RSS in this study confirmed this six-factor structure. Of the 164 Jewish participants, between 1.2% and 30.5% experienced various r/s struggles. Beliefs in a cruel God and distant God, religious participation, and fundamentalism predicted higher levels of different types of struggle. All six forms of struggle were correlated with greater psychological distress. In regression equations including r/s struggles and demographic and religious variables, Moral struggles predicted lower life satisfaction, Divine struggles predicted depressive symptoms, and both Divine and Doubt struggles predicted generalized anxiety. Possible explanations and implications of the findings are offered. We conclude by pointing to the limitations of the study and suggesting a few directions for future research.